Eruptive syringomas of the neck - Liliane Borik; Amy Spizuoco; Viktoryia Kazlouskaya (Our Dermatology Online, 2014)
Syringomas are benign adnexal tumors of eccrine origin. Eruptive syringomas clinically present as multiple, skin colored tiny papules that usually develop during a short period of time and are frequently misdiagnosed with other entities. Histopathological examination is essential in the diagnosis and usually reveals numerous, small ducts in the dermis lined with a double row of epithelial cells. Herein, we present an additional case of multiple eruptive syringomas on the neck in a 25 year old female.